The Reasons for Discontinuation of Infliximab Treatment in Patients with Crohn's Disease: A Review of Practice at NHS Teaching Hospital. (26th October 2011) - Krupa, Lukasz Z.; Kennedy, Hugh J.; Jamieson, Crawford P.; Fisher, Nicola; Hart, Andrew R.
Abstract : Introduction . There is little information on the reasons for discontinuing infliximab treatment in patients with Crohn's disease. The aim of this study was to document these reasons to determine if any were preventable which would allow patients to continue the therapy. Aims & Methods . A review of the medical notes was conducted at the Norfolk and Norwich University Hospital on patients with Crohn's disease treated with infliximab between 2002–2008 to determine the reasons for stopping it. Results . A total of 65 patients were identified who had treatment with infliximab, of whom 23 (35.3%) had their therapy stopped. The reasons for discontinuation of infliximab in the 23 patients were: 47.8% side effects, 17.4% refractory disease, 13.0% achieved remission and did not receive long-term maintenance treatment, 4.34% pregnancy, 4.34% death, and unknown 13.0%. Conclusions . The main reasons for the discontinuation of infliximab were side effects rather than a lack of clinical response.